Quality Seed Production in Two Medicinal Herbs: Osmium Sanctum (TULSI) and Solanum nigrum (MAKOY): Exploring Quality Seed Production in Medicinal Herbs (Journal of Advances and Scholarly Researches in Allied Education, 2014)
Seed Quality refers to a number of seed related properties which may have varying degree of practical importance for Agriculture and Medicine. Earlier people used to collect Medicinal plant from wild sources after that people started cultivation of these plant. Presently there is a great demand for Medicinal plant in the world market. Medicinal plant Cultivation is going in a commercial way .Quality seed is needed to cultivate the medicinal plants in commercial way .Medicinal and Aromatic plant research station Rajender Nagar Hyderabad is working on Quality seeds production of different Medicinal plants.